An Interpretation Of Qur’an, 22:73: A Biomedical Perspective - Abdillah Mussa Kitota (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
This was a systematic study design conducted to unravel the implications of the parable: and if the fly snatches away a thing from them, they will have no power to release it from the fly (Qur’an, 22:73). Famous tafseers of Qur’an were used to provide the preliminary interpretation of this verse and the link between this parable to the findings in biomedical sciences. Data concerning what have been implicated in this parable were screened from online biomedical databases such as PubMed, PubMed Central, Google Scholar, and Science Direct. Keywords words and keywords combination used were: fly, house fly, feeding mode of house fly, digestion of house fly, house fly as vectors, house fly + disease transmission, and diseases caused by house fly. Only articles related to fly’s feeding, digestion, harboring and transmission of diseases; that were published from 2000 onwards, were selected. More than 100 articles were collected, and Thematic analysis method was used to disclose how the wording of the Qur’an in this parable have traversed the findings in the biomedical sciences. Finally, 40 articles were selected. The findings show that there are two things that a fly can snatches from us; that we will have no power to get them back from it: (1) food, (2) health and life. For the food, they don’t take solid food, rather, they dissolve it before ingestion, then they absorb its liquid. For health and life, they harbor more than 100 pathogens; and transmit more than 100 diseases, that have led to a very great burden of hospitalization, disabilities and loss of lives. This review study may lead to contemplation that will increase faith. It may also help the idol worshippers to abandon their false deities, and turn towards Allah (S.W.T).